Sensitivity of the IRD whole-body counter for in vivo measurements in the case of accidental intakes (Brazilian Journal of Radiation Sciences, 2017)
Intakes of radionuclides by humans may occur in the fuel cycle, nuclear medicine, biological research and in TENORM industries and in case of accidents involving workers and the general public. In vivo monitoring is recognized as a useful tool for the evaluation of such exposures. The IRD whole-body counter consists of a shielded room equipped with four HPGe and two NaI(Tl) detectors. The system is able to identify and quantify photon emitters in the range from 10 to 3000 keV. The minimum detectable activities for most of the radionuclides of interest allow occupational monitoring as well as evaluation of accidental intakes.